(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
extract The purpose: of the research is to show the importance of the letter of guarantee platform as an electronic supervisory control for managing the process of issui isng letters of guarantee and limiting fraud and forgery operations, and to determine the impact between the independent variable of the letter of guarantee platform in light of banking legislation with its dimensions of (traditional issuance procedures before the platform and issuance procedures after the platform, and the position beneficiariesies), and the dependent variable reducing the risks of letters of guarantwith in idimensionons of (centralization of the decision), identifying the reasons for resorting to the use of the letter Andand the research problem has been identifi is the adequacy of the electronic platform in reducithe riskssks of letters of guarantee? In solving its problems, the research was based on a hypothesis: correlation and influence, where the first main impact hypothesis was: "There is no statistically significant effect of the issuance of traditional letters of guarantee (X) in reducing the risks of letters of guarantee (Y)", and the second hypothesis was: "There is no effect of statistically significant significance of the issuance of letters of guarantee after the electronic platform (Z) in reducing the risks of letters of guarantee (Y)", and the research adopted the method of the inductive approach: in the theoretical side to review the research problems and prove its hypotheses to achieve the objectives of the research Descriptive-analytical: The relationship supported by the quantitative aspect of analyzing the annual financial statements of private commercial banks, the research sample before and after the platform (2017-2021), which represented the first community of the research sample and numbered six commercial banks, field visits and personal interviews with the Central Bank of Iraq As the entity responsible only for managing the platform, as well as the statistical tests of the second community of the research sample to measure the attitude of the beneficiaries towards the letters of guarantee platform, the questionnaire was adopted as a research tool for the purpose of With the data from the sample of 50 individuals, i.e., 87% of the total study population, in the administrative levels (senior management, middle management, and executive) in a number of beneficiaries, the questionnaire was used as a means to obtain data from the sample of 50 people"by the beneficiaries represented by the ministries and their departments, and the paragraphs of the questionnaire were analyzed based on the statistical programs:SPSS,version 26; (Exce;) and(Amo) Security in the Iraqi banking environment and a steptowardr applying electronic governanc The research reached a set of results, the most prominent of which were: The weakness of the centralization of the decision and the procedures followed for the issuance process for letters of guarantee before the platform contributed to the expansion of risks for letters of guarantee, and in addition, the "Letters of Guaranteeplatform"m contributed more broadly In ensuring the rights of the beneficiaries due to electronic supervisory oversigh, and recommendation, it is necessary: to develop the platform’s work and work to create an additional field in the platform and develop it in broader areas by making the customer’s account linked to the platform to support customer operation. Finance Finance, as well as "documents related to in-kind guarantees,especially real estate that is mortgaged,y" areprovided with the validity of electronic issuance with the availability of advanced means to detect them if theyd areforged to encourage the use of technology more widely in state departments andf electroniccontrol and to achieved electronic governance, and accordingly the research structure consisted of fou chapterss: the first axis is the research methodolog;, the second axis is the theoretical aspec;, the third axis is the practical aspect of the researc;, and the fourth axis is the conclusions and recommendations.